Perancangan dan Implementasi Virtualisasi Server Dengan Citrix Xenserver di PT. PLN Wilayah Semarang - Slamet Handoko (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2014)
Nowadays the need for information technology is growing rapidly , especially the need for a server as a medium for the passage of an application , in addition , there are constraints of the most important in the utilization of information technology at this time that the resource requirements are not cheap and space constraints, it is necessary utilization of resources as much as possible. Virtualization as a part of information technology is expected mamapu overcome the existing problems. If seen as part of an overall trend in a particular company PT. PLN (Persero) which use autonomic computing, a scenario in which wherein the IT environment will be able to manage itself based on perceived activity and utility computing, where processing power omputer considered a utility that clients can pay only used alone. Implementation of virtualization with Citrix XenServer based on Linux itself aims to centralize administrative tasks to improve scalability and also as part of the company's efficiency. The methodology used for this study is NDLC which has 6 phases namely, analysis, design, prototype simulation, implementation, monitoring and management, with the implementation of this system deiharapkan able to meet the needs of corporations.